Biomedical effects of Laurus nobilis L. leaf extract on vital organs in streptozotocin-induced diabetic rats: Experimental research. (January 2021) - Mohammed, Rebin Rafaat; Omer, Abdullah Khalid; Yener, Zabit; Uyar, Ahmet; Ahmed, Avin Kawa
Abstract: Diabetes mellitus (DM) has been treated with herbs for centuries and many herbs reported to exert antidiabetic activity. Laurus nobilis is an aromatic herb belonging to the Lauraceae family, commonly known as bay. This study aimed to investigate the activity of Laurus nobilis leave extracts on histopathological and biochemical changes in β-cells of streptozotocin (STZ)-induced diabetic rats. Thirty healthy adult male albino rats were included in the study and divided equally into 5 groups for 4 weeks as follow; control group (C), diabetic group (D), diabetic Laurus nobilis extract group (DLN), Laurus nobilis extract group (LN) and diabetic acarbose (DA) group. Histopathologically, D group rats exhibited various degenerative and necrotic changes in their liver, pancreas and kidney, whereas the DLN rats had nearly normal histology. Insulin immunostaining in the pancreatic beta cells was decreased in the D group compared to the C group, whereas the DLN group was similar to the C group. The glucose concentration decreased significantly in both diabetic rats treated with L. nobilis and acarbose ( p  < 0.05). Additionally, the levels of aspartate aminotransferase (AST), gamma-glutamyltransferase (GGT) and alanine aminotransferase (ALT) enzyme were significantly decreased in both diabetic rats treated with L. nobilis and acarbose, compared to the D group ( p ˃ 0.05). Outcomes of this study said that leave extracts of L. nobilis has valuable effect on blood glucose level and ameliorative effect on regeneration of pancreatic islets, it also restored the altered liver enzymes, urea, creatine kinase, total protein levels, calcium and ferritin to near normal. Highlights: Diabetes mellitus has been treated with herbs for centuries and many herbs reported to exert antidiabetic activity. Historically, traditional herbal treatments have been shown to possess successful pharmacological activity, such as in the case with metformin, isolated from Galega officinalis. Laurus nobilis has a valuable effect on blood glucose level and ameliorative effect on regeneration of pancreatic islets. Laurus nobilis have also been shown to display insulin-enhancing activity in vitro. Laurus nobilis also restored the altered liver enzymes, urea, creatine kinase, total protein levels, calcium and ferritin to near normal.